Rice straw open burning in Kedah and Perlis during harvesting season for 2015 and 2019 / Siti Nurquratulain Mohd Khalis - Mohd Khalis, Siti Nurquratulain (2020)
Open burning of rice straw is practiced in many countries and has been proven as a significant source of air quality affection which mostly during the harvest season. Excessive of this activities often leads to haze that can affect the main road and residential area nearby. This study aimed to estimate the variation on rice straw open burning in year 2015 and 2019 at Kedah and Perlis regions. In achieving the aim, the objectives of this study are to analyze the trends of rice straw open burning. Besides, this study needs to observe the relationship between Land Surface Temperature (LST) and Air Pollution Index (API) in two distinct years which are year 2015 and 2019. For processing, Erdas Imagine and ArcMap is being used. The state of Perlis and Kedah has been chosen as the study area, in correlation to the paddy planting is the main economic sources for both states. API data collected from Jabatan Alam Sekitar and online data from Unit Pemodenan Tadbiran Dan Perancangan Pengurusan Malaysia (MAMPU) webpage are bring together. The map of spatial distribution based on API and the relationship graph of LST and API of Kedah and Perlis in 2015 and 2019 is shown as the result. This study is significant to provide an awareness and proof that one of the cause of temperature rise is open burning of rice straw to the paddy farmers together with the community. Last but not least, this study can help in enhancing the rice straw management in Kedah and Perlis.